Diatomáceas epilíticas de riachos subtropicais com altas concentrações de Alumínio e Ferro, Sul do Brasil - Amaral, Mailor Wellinton Wedig (2021)
Epilithic diatoms are photosynthetic microorganisms growing attached to rocky substrate. Taxonomic studies approaching diatom floras are crucial for describing new species, as well as recognizing environmental stresses and assessing the ecological status of aquatic systems. This work aimed to conduct a taxonomic survey of epilithic diatoms from a hydrographic microbasin in southern Brazil with naturally high iron and aluminum concentrations. Sampling of rocks, water and sediments were carried out from 2016 to 2019. Diatom samples were oxidized and analyzed using light and scanning electron microscopy. The first article deals with the description of a new species of the genus Nupela, which was found in streams with acidic–neutral pH, low conductivity and low to high nutrient concentrations. In the second article we identified 221 diatom species at infrageneric level, focusing on their teratological forms and characterizing the limnological conditions and metal concentrations where they were found. Fragilaria spectra, Fragilaria tenera var. nanana and Humidophila arcuatoides were firstly recorded in the state of Paraná, and Pinnularia laucensis represent a new record for Brazil. We found teratological valves in 34 taxa, containing modified outline, changes in the striae pattern, and doubled central area. The metals and environmental variables in the Cascavel River microbasin probably contributed to the diatom teratologies. Our work contributes to the taxonomic knowledge of epilithic diatoms in the region, as well as extending the record of teratological taxa in the literature.